The autobiography of Martin Luther King - Carson, Clayborne (New York Intellectual Properties Management in association with Warner Books, 1998)
The mild-mannered, inquisitive child and student who rebelled against segregation; the dedicated young minister who constantly questioned the depths of his faith and the limits of his wisdom; the loving husband and father who sought to balance his family's needs with those of a growing nationwide movement; and the reflective, world-famous leader who was fired by a vision of equality for people everywhere. Relevant and insightful, this autobiography offers king's seldom discussed views on some of the world's greatest and most controversial figures including John F. Kennedy, Malcolm X, Mahatma Gandhi and Richard Nixon. This book brings to life a remarkable man whose thoughts and actions still inspire our desires, hopes and dreams.
Includes bibliographical references (p. [371]-390)
Keywords: King, Martin Luther, Jr., 1929-1968. African Americans-Biography. Civil rights workers-United States -Biography. Baptists-United States-Clergy -Biography. African Americans-Civil rights -History-20th century